Infundios y verdades. EpIfanio de Salamina y el evangelio de Judas - Rodríguez Gervás, Manuel (ARYS. Antigüedad: Religiones y Sociedades, 2020)
The fourth century was a period of growth and political influence of the Christian Church. Some Church Fathers worked to refute theological and dogmatic errors and in this way put an end to all kinds of heresies threatening a break-up. Among these was Epiphanius of Salamis, who in his Panarion describes and attacks a group called “Cainites”, who followed a work known as the Gospel of Judas. In this study an attempt is made to analyse the truths and falsehoods present in Epiphanius’ work relating to this gospel.
Keywords: 4th century; christianity; gnosticism; heresies